MUI fatwa in legitimating government regulations about covid-19 in Indonesia - Hasan, Nur; Munir, M. Misbakul (NUsantara Islamic Economic Journal, 2024)
This research aims to analyze the MUI Fatwa in legitimizing Government Regulations in breaking the Covid-19 chain. By using a qualitative approach and using library research, research can examine data related to the object of study being compiled. By using existing research data and literacy studies, the author can conclude that the MUI Fatwa's decision to allow the use of vaccinations and worship procedures during the pandemic is appropriate, as a step to break the chain of spread of Covid-19. This decision was made in order to support government programs through regulations issued to create herd immunity for the community and make the pandemic status endemic.